Investigation on Super-Resolution Focusing Performance of a TE-Polarized Nanoslit-Based Two-Dimensional Lens - Zhu, Yechuan (Nanomaterials (Basel), 2019)
Conventional optics suffer from the diffraction limit. Our recent work has predicted a nanoslit-based two-dimensional (2D) lens with transverse-electric (TE) polarized design that is capable of realizing the super-resolution focusing of light beyond the diffraction limit in the quasi-far field. Furthermore, the super-resolution capability can be kept in a high-refractive-index dielectric over a wide wavelength range from ultraviolet to visible light. Here, we systematically investigate the influence of various factors on the super-resolution focusing performance of the lens. Factors such as lens aperture, focal length and nanoslit length are considered. In particular, the influence of nanoslit length on lens focusing was ignored in the previous reports about nanoslit-based 2D lenses, since nanoslit length was assumed to be infinite. The numerical results using the finite-difference time-domain (FDTD) method demonstrate that the super-resolution focusing capability of a nanoslit-based 2D lens increases with the lens aperture and reduces with the increase of the lens focal length. On the other hand, it is notable that the length of the lens focus is not equal to but smaller than that of the nanoslits. Therefore, in order to achieve a desired focus length, a lens should be designed with longer nanoslits.